Climate change impacts in El Salvador’s economy: The agriculture sector - Salazar, Mauricio; Thomas, Timothy S.; Dunston, Shahnila; Nazareth, Vijay (International Food Policy Research Institute, 2019)
This report finds that by 2050 the negative effect of climate change on agricultural productivity in El Salvador will be among the highest in the region. Of the food crops, sorghum will have losses due to climate at around 14 percent; maize at 13 percent; and rice at 11 percent. Sugar cane will potentially lose 36 percent due to climate change. Furthermore, El Salvador will possibly be the country hit harder in the coffee sector than any other country in the world, with a loss of more than 35 percent of the suitable coffee growing area (Ovalle-Rivera et al. 2015). Livestock productivity, as well, will be impacted by the higher temperatures. Recommendations for policy makers are presented that will help deal with the multi-pronged threat that climate change brings to the agricultural sector of El Salvador.